An interference and load aware routing metric for Wireless Mesh Networks. (3rd January 2011) - Nguyen, Lan Tien; Beuran, Razvan; Shinoda, Yoichi
This paper proposes a load and interference-aware routing metric for wireless mesh networks, named Channel Utilisation and Contention Window Based (C2WB) metric. Our metric assigns weights to individual links which are proportional to the links service times estimated from both channel utilisation and the average contention window of the CSMA/CA mechanism. The path metric, combined from individual link weights, accounts for both load and interference of the links on the path. Thus the C2WB metric helps the routing protocol to balance the traffic and to improve the network capacity by avoiding routing the traffic through congested areas.